Comparison of Environmental Care Attitude of Adiwiyata and Non Adiwiyata School Students in Jember - Setyawati, Heni; Maisyaroh, Wiwin (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2023)
This aims of this study was to compare the environmental care between students attending Adiwiyata schools and those attending non-Adiwiyata schools. The research method used the comparative method. Sampling in research used purposive sampling technique. The sample consisted of Adiwiyata school students, SMP N 2 Balung with a total of 61 students and non-Adiwiyata students SMP N 9 Jember with a total of 57 students. Data collection techniques used a questionnaire. The normality test used the Kolmogorov-Smirnov test, and the homogeneity test used the Levene Statistics. The research hypothesis was tested using the Mann Whitney test, after the hypothesis testing was calculated, it was obtained if the sig. (2-tailed) > 0.05 then Ho is accepted and Ha is rejected. Meanwhile, if the sig. (2-tailed) < 0.05 then Ho is rejected and Ha is accepted. Referring to the Mann Whitney analysis, it could been seen that sig.(2-tailed) is 0.588 > 0.05. Because of that, H0 was rejected and Ha was accepted. So the conclusion of this research was that there are differences in environmental care between students who attend Adiwiyata schools and non-Adiwiyata students.